Phylogenetic analysis of Infectious Bursal Disease viruses according to newly proposed model of classification into geno-groups - Rai S. Ali Khan; Mudasser Habib; Waqas Ali; Muhammad Salah Ud Din Shah; Asma Ashraf; Zahid Ali Tahir; Zeinab H. Helal; Mazhar I. Khan; Shahid Mahboob; Khalid A-; Fahad Al-Misned (Elsevier, 2019)
Background: Infectious bursal disease virus (IBDV) is the causative agent of Infectious Bursal Disease (IBD), the disease causes immunosuppression which leads to secondary infections among rearing poultry flocks. Characterization of the virus is important for its control and eradication. The circulating IBDVs are classified on the basis of their antigenic and pathogenic properties. The virus is categorised as classical, variant and very virulent IBDV (vvIBDV). IBDV is a non-envelop, icosahedral double stranded virus. Viral protein 2 (VP2) is the major structural protein of capsid that determines the host-pathogen relationship. The aim of this study was to characterise the IBD virus of Pak-Asian region. Methodology: IBDV suspected flocks were examined in Punjab, Pakistan from 2014-2018. Two hundred and fifty samples were collected with complete history of the disease. The suspected samples were collected from broiler, layer and rural poultry farms. RNA was extracted and hyper-variable region of VP2 gene was amplified using specific primers. Nucleotide sequence of the VP2 gene was determined and its Amino Acid sequence was deduced. Moreover, phylogenetic analysis was also performed. Results: The current classifications based in a hyper-variable region of the capsid protein VP2 (hvVP2), classification of IBDVs is split into newly proposed geno-groups according to Jackwood group. Among these prevailing, some IBDVs are limited geographically whereas, others are reported cosmopolitan. Genetic alterations are continuously playing role in evolution of new strains of the virus. Conclusion: During this study it was found that isolates of IBDV fall in first three geno-groups. Most of the geno-groups are prevalent around the world, whereas the mutated and re-assorted ones are confined in particular areas of the globe. Keywords: IBDV, Classification, Geno-groups, Pak-Asian region, Phylogenetic analysis